The Effect Of ND:YAG Laser On Enamel Surface And Composition For Removal Of Composite Adhesives - Abd Razak, Nurul Atiqah (2018)
Nd:YAG laser (1064 nm) irradiation on enamel surface and removal of composite adhesives was studied. Field Emission Electron Microscopy (FESEM) and Energy Dispersive X-Ray (EDX) analysis were used to observe the changes in surface morphology and composition of elements on the tooth surface. Carbon, oxygen, phosphorus, and calcium were the elements identified in the samples. In this study, the effect of Nd:YAG laser parameter such as fluence, pulse width and energy were investigated. Forty healthy premolars were cut into half and subjected to Nd:YAG laser irradiation.